Overall thermal transfer value of residential buildings in Malaysia - Saidur, Rahman; Hasanuzzaman, M.; Hasan, M.M.; Masjuki, Haji Hassan (Journal of Applied Sciences, 2009)
This study presents the Overall Thermal Transfer Value (OTTV) and the energy consumption of room air conditioners of the residential buildings in Malaysia. A survey has been conducted to investigate the OTTV and the energy consumption of room air conditioners of the residential buildings in Malaysia. OTTV calculation, energy consumption and effect of the building parameters on energy consumption have been investigated. It is found that OTTV of the residential buildings in Malaysia varied from 35 to 65 W m -2 with a mean value of 41.7 W m -2. The sensitivities of several parameters such as window to wall ratio (WWR), Shading Coefficient (SC), U-value for wall (U w) and solar absorption (Î±) are provided to design and optimize the thermal performance of residential buildings. It is found that U and Î± influence more on OTTV compared to other parameters. The analysis shows that about 14, 10 and 5 of residential building air conditioners have annual electricity consumption in the ranges 500 to 1000 kWh, 1000 to 2000 kWh and 7500 to 10000 kWh, respectively. The maximum, minimum and average annual electricity consumption of the air conditioner of residential buildings is 22055.5, 136.1 and 3708.8 kWh, respectively. Â© 2009 Asian Network for Scientific Inform